Sifat Fisik Dan Mekanik Papan Komposit Dari Serat Tandan Kosong Kelapa Sawit (TKKS) Hasil Penguraian Secara Mekanis Dengan Perekat Gambir - Junaidi - - (Jurnal Ilmiah Poli Rekayasa, 2020)
Oil palm empty fruit bunches (OPEFB) are a solid waste product from the oil palm industry that are about 70% fiber. Previous research has indicated that this fiber can be used to produce composite board. Gambier can be used in an adhesive to produce these boards as it has strong adhesive properties. This research investigates the suitability of four types of OPEFB fiber resulting from different mechanical separation speeds and three adhesive made from differing concentrations of Gambier (12%, 14%, 16%) to produce high quality composite board. The results of the research suggest the type of the fiber and the concentration of the gambier used significantly influence the density of the resulting board and that there are interactions between these two variables. The water content of the board is significantly influenced by the type of OPEFB fibre but not by the concentration of gambier or any interaction between these variables. Thickness swelling, modulus of rupture (MOR) and modulus of elasticity (MOE) are all influenced by type of fiber and concentration of gambier without any significant interaction between these two factors. The best types of fiber was those labeled A and B. The best performing composite board was produced from the longer B fibers and 16% gambier adhesive. This board a had density of 0.86 g/cm3, MOR 251.3 kg/cm2 and strength parallel to the grain of 145.6 kg/cm2. This data suggests that the density, water content and MOR of the boards made with this combination of material meets standard SNI 03-2105-2006 however the thickness swelling of the board fails this standard.